Influence of Markowitz Method Risk and Return Calculations as a Basis for Investment Decisions in BEI BUMN Shares 20 Period 2019-2022 - Paramida, Novia; Mukti, Chandra Fitriyani Crisna; Maharani, Dorifahtu Afirstantian; Pandin, Maria Yovita R. (PT. Riset Press International, 2024)
The aim of writing this scientific article is to determine the influence of the Markowitz Method of risk and return calculations on Investor Rationality for the Security of Investing in 20 BUMN IDX Shares for the 2019-2022 Period. The method used in this research is a descriptive method with a quantitative approach. The type of data used is secondary data which takes data from the official website idx.com and also investing.com. The sample used was 20 state-owned companies. The data collection technique in this research is by using documentation techniques. The data collection process consists of: calculating the expected return for each company, conducting statistical tests using SPSS 24, and finally conclusions. The results of this research are that the Markowitz method of calculating risk & return has a significant effect on investors' rationality in investing in BUMN 20 shares.